Single nucleotide polymorphisms in the NOS2 and NOS3 genes are associated with exhaled nitric oxide. Issue 3 (24th February 2012) - Dahgam, Santosh; Nyberg, Fredrik; Modig, Lars; Naluai, Åsa Torinsson; Olin, Anna-Carin
Abstract : Background: Polymorphisms in nitric oxide synthase genes ( NOS1, NOS2, and NOS3 ) have been suggested to have a major impact on fraction of exhaled nitric oxide (FENO), a biomarker of airway inflammation. However, the genetic contribution of NOS polymorphisms to FENO is not fully understood. The aim of this study was to investigate comprehensively the association between single nucleotide polymorphisms (SNPs) in all three NOS genes and FENO in an adult population, and to assess whether such associations are modified by asthma or atopy. Method: In 1737 adults from a Swedish general population sample, FENO was measured and genetic variation in the NOS genes was assessed using 49 SNPs. The genetic effect of NOS polymorphisms on FENO, asthma, and atopy was estimated using multiple regression methods. Results: In a multi-SNP model based on stepwise regression analysis, two SNPs in NOS2 and one in NOS3 showed independent associations with levels of FENO. For NOS2 SNP rs9901734, subjects had 5.3% (95% CI 1.0% to 9.7%) higher levels of FENO per G allele, and for rs3729508, subjects with CC or CT genotypes had 9.4% (95% CI 3.1% to 15.2%) higher levels compared with TT. For NOS3 SNP rs7830, subjects with GT or TT had 5.6% (95% CI 0.4% to 11.1%) higher levels than GG; the genetic effect of this SNP was stronger in asthmatics (21.9%, 95% CI 4.6% to 42.0%). Conclusion: These results suggest that NOS2 is the major NOS gene determining variability in exhaled nitric oxide in the healthy adult population, while NOS3 may play a more important role in asthmatic adults.